مقولات ما بعد الحداثة في النقد العراقي المعاصر (اللاتمايز وتذويب الحدود الفاصلة) أنموذجا - Saleh, فرح مهدي; Abdul Hassan, ريام (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
There has been a metaphorical movement with tools witnessed in literary texts in the postmodern era. Its manifestations appeared in poetry and narrative in the form of intentional dissolving of the identities of borrowed texts into the identity of poetry or narrative. Postmodernism has shattered the boundaries between the everyday and the aesthetic, the author and their work. As a result, we now receive a blend of arts melted within the crucible of poetry, which now approaches its reader through a pictorial artwork, interactive digital performance, or engagement in a written space with deliberate semantic intentionality in vision and formation, across the distances of black and white, and other metaphors witnessed in postmodern poetic discourse. In terms of narrative, there is a borrowing of tools from other arts and an overlap with other genres different from the essence of narrative. This seems to be due to the narrative works, especially the novel, being capable of encompassing all arts in its narrative structure, as it is a complete imaginary world between two covers.